Propriedade intelectual com ênfase em trade secrets : criptologia e performance econômica - Santos, Júlio César dos (2003)
This work presents a theoretical approach on intellectual property with emphasis in trade secrets as entry barriers. Progress in cryptology in the field of the mathematics can be added to the theoretical efforts developed in microeconomics in industrial organization. In this context, cryptology is rescued historically and its main functions are presented in the intellectual property, especially in trade secrets. This research questions: Why do the firms cryptograph their productive processes? Has intellectual property, especially trade secrets, been playing an important role as a barrier to entry in the contemporary economy? How can cryptology and its respective developments in mathematics contribute to the strengthening of the industrial secret? It is noticed that in spite of the outstanding presence of cryptography and of the incorporeal goods in the contemporary economy, the theoretical analyses are still scarce, as are case studies and databases on intellectual property and mainly, on trade secrets. This research contributes to explication of its concepts and warns about the importance of intensification of scientific research on this topic, in order to reach a better understanding of managerial economical dynamics at the present time.